Cognitive Metonymic Models of ‘Hollywood’: Corpus Analysis (Proceedings of Southern Federal University. Philology, 2020)
Within the framework of cognitive linguistics metonymy exists only between concepts belonging to the same Idealized Cognitive Model (ICM). Metonymic relationships between concepts are not chaotic but regulated by a set of cognitive and communicative principles. They dictate the choice of metonymic source and metonymic target. Cognitive linguistics also assume, that we think in terms of metaphor and metonymy, so they are not examples of our creativity in figurative language, but regular, standard and default. This fact is proven by numerous data from text corpora. The case study of the article is the ICM ‘Hollywood’ and its metonymic models.Key words: idealized cognitive model, metonymy, cognitive linguistics, communicative principles, cognitive principles.DOI 10.18522/1995-0640-2020-2-63-70